Implementation of the Theory of Planned Behaviour on Entrepreneurial Intention - Krido Eko Cahyono; Nanik Hariyana; Muhammad Tahajjudi Ghifary (JURNAL EMA (Ekonomi Manajemen Akuntansi), 2025)
This study aims to examine the impact of entrepreneurship education on the entrepreneurial intentions of university students in Surabaya. Purposive sampling was applied to a group of 200 college students. The sample criteria included students who had completed entrepreneurship courses for bachelor's degrees and entrepreneurship practicums for vocational programs. This research utilized the Mann-Whitney U-Test via SPSS and partial least squares analysis through SmartPLS. The results of this research indicate the following: 1) attitude, subjective norm, and perceived behavioural control positively and significantly influence entrepreneurial intention, 2) entrepreneurship education significantly and positively affects entrepreneurial intention, 3) entrepreneurship education did not moderate the impact of any theory of planned behaviour variables on entrepreneurial intention, 4) gender did not moderate the relationship between entrepreneurship education and entrepreneurial intention, 5) no difference was found in the entrepreneurial intention levels of male and female college students, 6) no distinction was observed in the entrepreneurial intention levels of bachelor's degree students compared to vocational studies students.